Kerouac Ascending : Memorabilia of the Decade of On the Road. - Lenrow, Elbert (Cambridge Scholars Pub., 2010)
Kerouac Ascending: Memorabilia of the Decade of ON THE ROAD is a memoir written by Elbert Lenrow about his relationship with Jack Kerouac, whom he taught at the New School in NewYork when Jack was emerging as a writer and with Allen Ginsberg, both of whom Lenrow befriended and encouraged. Lenrow writes with sympathy and charm about both writers and their "beat" friends, revealing Kerouac's seriously academic side by sharing papers he wrote in his course and giving insight about both writers t ...